DEVELOPMENT OF SCIENCE LEARNING MATERIAL WITH SOCIO-SCIENTIFIC ISSUES (SSI) ON CLIMATE CHANGE MATERIALS TO IMPROVE SCIENCE LITERACY OF JUNIOR HIGH SCHOOL STUDENTS - Yaumi, Yaumi; madlazim, Madlazim; Taufikurohmah, Titik (Jurnal Penelitian Pendidikan IPA, 2019)
This research aims to produce IPA learning devices with the approach of Socio-Scientific Issues (SSI) on climate change materials to improve the science literacy of Junior high school students. The learning devices developed are syllabus, learning Implementation Plan, Student teaching materials, Student Worksheets, and Science literacy test. This type of research is development research with the model Dick and Carey. Test learning devices in the classroom using one group pre-Test post-Test design. The research instruments in this study are validation sheets, learning implementation observation sheets, activity observation sheets, test sheets, and student response polls. Data collection using validation methods, observations, tests, and polls. Data analysis techniques use quantitative descriptions. The results of the study show that learning devices are declared worthy of validity, practicality, and effectiveness. The validity aspect indicates that the learning device is very valid and reliable. The practicality aspect of the practice of learning has an average 3.66 with excellent criteria and an student activity is very active. The average achievement of science literacy from 32 students in class VII A when pre-test was at level 2 experienced an increase when post-test was at level 4. Based on N-Gain test the value of 0.50 is on medium criteria. Students ' response to the application of a Socio-Scientific Issues (SSI) approach to climate change material is very good.  Learners give a positive response of 87.60%.